Impact of florpyrauxifen-benzyl on hybrid rice seeded at different densities - Thomas W. Eubank; Jason A. Bond; Tom W. Allen; Bobby R. Golden; Victor F. Carey; Darrin M. Dodds; Hunter D. Bowman (Weed Technology)
Florpyrauxifen-benzyl is a postemergence rice herbicide that has reduced rice yield in some situations, and producers are concerned that the impact could be even greater with low rice seeding densities. Therefore, research was conducted in Stoneville, MS, from 2019 to 2021, to evaluate the effect of florpyrauxifen-benzyl on rice yield when a hybrid was seeded at reduced densities. Rice cultivar FullPage RT 7521 FP was seeded at 10, 17, 24, 30, and 37 kg ha−1. At the 4-leaf to 1-tiller growth stage, florpyrauxifen-benzyl was applied at 0 or 58 g ai ha−1. Rice injury following application of florpyrauxifen-benzyl was ≤8% across all seeding rates and evaluation intervals. Application of florpyrauxifen-benzyl reduced plant heights by 14% to all seeding rates but did not result in delayed rice maturity. When florpyrauxifen-benzyl was not applied to rice that was seeded at 10 and 17 kg ha−1 seeding rates, rice matured slower than when it was seeded at 24, 30, and 37 kg ha−1. When florpyrauxifen-benzyl was applied, rough rice grain yields were reduced by at the 17 and 37 kg ha−1 seeding rates, but not at any other seeding rate. In conclusion, application of florpyrauxifen-benzyl at a 2× rate can cause a loss of yield resulting from variation in rice densities.